The identity of Nanorana yunnanensis (Anderson, 1879) from Thailand, with a description of its tadpole (Anura, Dicroglossidae) - Thongproh, Prapaiporn; Chunskul, Jidapa; Makchai, Sunchai; Cota, Michael; Safoowong, Mongkol; Duengkae, Prateep; Duangjai, Sutee; Thitichayaporn, Somsak; Chuaynkern, Yodchaiy; Chuaynkern, Chantip (Zootaxa, 2023)
Nanorana yunnanensis has been reported in Thailand for many years; however, no specimens have been verifiably described. To verify the identity of this species in Thailand, we observed Thai specimens formerly assigned to the species N. bourreti and N. yunnanensis. The 12S rRNA, 16S rRNA, and ND2 mitochondrial genes were used to clarify the taxonomic statuses of the Thai specimens. The results showed that our specimens formed a clade with N. yunnanensis, containing specimens from southern Yunnan and Vietnam. The respective mean sequence divergences of the 12S and 16S rRNA genes between populations from Thailand versus China were 0.59% and 1.09%, for populations from Thailand versus Vietnam were 0.57% and 0.61%, and for populations from China versus Vietnam were 0.59% and 1.09%. We provide descriptions of the tadpole and adult specimens of N. yunnanensis from Thailand.